KEPALA DESA PEREMPUAN DAN TATA KELOLA INKLUSIF: INTEGRASI PRINSIP GENDER EQUALITY, DISABILITY, AND SOCIAL INCLUSION (GEDSI) DALAM PENGELOLAAN DANA DESA DI KABUPATEN KEPULAUAN TALAUD - Katerina Bataha; Very Y Londa; Sintia M Rawis (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study explores the role of women village heads in promoting inclusive governance by integrating Gender Equality, Disability, and Social Inclusion (GEDSI) principles into village fund management in the border areas of Talaud Regency. The research is grounded in the urgency to understand how women’s leadership contributes to equitable decision-making and inclusive development at the grassroots level, particularly in geographically isolated and underdeveloped regions. Using a qualitative method with a case study approach, the study collected data through in-depth interviews, direct observations, and documentation involving women village heads, community members, and local government representatives. The findings reveal that women village heads demonstrate strong participatory leadership, emphasizing transparency, accountability, and inclusiveness in managing village funds. They actively ensure that development programs address the needs of marginalized groups, including women, people with disabilities, and people with low incomes. However, the study also identifies challenges such as limited capacity in financial management, cultural barriers, and gender bias that hinder optimal GEDSI implementation. The research underscores that strengthening institutional support and capacity-building initiatives is crucial to sustaining inclusive governance practices. Overall, women’s leadership in Talaud’s border villages plays a pivotal role in fostering equitable development and advancing the GEDSI agenda in local governance.